The evaluation concepts – a necessary means of achieving the constitutional idea of legal certainty or a factor leading to its violation? - S. S. Burtseva (Правоприменение, 2024)
The subject of the research is the study of evaluative concepts included by the legislator in legal norms in order to ensure dynamic legal regulation of social relations. The problem of using evaluative concepts is of scientific interest, since the unreasonable inclusion of such concepts in the content of a legal norm can lead to a violation of the constitutional idea of legal certainty, and their interpretation and practical application to specific situations largely depends on the level of legal awareness of the law enforcer.The author aims to analyze approaches to understanding the category of “evaluative concepts”, identifies signs that characterize this category, its role in the legal regulation of social relations.The methodology of scientific research is represented by a complex of private scientific, formal legal, systemic and structural methods.The main results. The author establishes the features of the inclusion of evaluative concepts in the legal norms based on the analysis of the practice of the Russian Constitutional Court, provides interesting cases considered in the framework of the constitutional proceedings. In particular, the author provides examples of the inconsistency between established judicial practice and the practice of the Russian Constitutional Court, and also establishes the need to apply evaluative concepts in both private and public law.Conclusions. The inclusion of evaluative concepts in legal norms is relevant for many areas of law, which is due to the need to ensure the flexibility and dynamism of legal regulation. However, the possibility of their application should not be unlimited, since this may lead to a violation of the fundamental principles of law, including the principle of legal certainty.